The Influence of Pile-Beam-Arch Construction on the Stratum and Station Support Structure. (30th January 2023) - Liu, Nan; Tong, Xiao; Chang, Longfei; Lv, Yong
Abstract : The PBA construction method is suitable for urban subway construction in situations with dense traffic and many surrounding buildings and can effectively reduce surface disturbance and control surface subsidence. Based on field-measured data, this study creates numerical finite element models of 3D stratum-structure, studies the influence of each process conversion on the subsidence of the ground surface and the force of the station supporting structure during the construction of the PBA station, and clarifies the optimal construction parameters. The research results show that the consistency between the field monitoring data and the simulation data is more than 80%, which verifies the correctness of the model. It is concluded that the formation of the pile-beam-arch is the main part of the supporting structure and that digging the pilot tunnel and the formation of the beam arch are the control factors of surface settlement. Based on this, the best sequence of pilot tunnel excavation and arch buckle of the two-story two-span station is obtained, and the optimal pilot tunnel excavation scheme of first the middle and then the side, first the upper and then the lower, and the best arch buckle scheme of the synchronous arch buckle on both sides is determined. The results of the research can serve as a guideline when selection the construction parameters for similar PBA stations.